Airflow Channel-Integrated Structured Fabric for High-Efficiency Solar Desalination - Polonia, Betti Ses Eka; Yuswanda, Ikko; Jamasri, Jamasri; Fikry, M J Mohammad; Muflikhun, Muhammad Akhsin (JMPM (Jurnal Material dan Proses Manufaktur), 2026)
The global shortage of freshwater and energy issues require the advancement of sustainable desalination technologies. This work introduces a novel structured fabric combined with an airflow channel for enhanced solar steam generation (SSG) efficiency. The instrument employs a synergistic composite of carbon fiber, serving as a wide-band photothermal absorber, and Tencel, which facilitates rapid capillary water movement due to its hydrophilic cellulose structure. Engineered airflow channels were incorporated into the evaporator design to surmount the thermodynamic limitations of stagnant vapor boundary layers. The findings indicate that a 5 mm channel width offers the ideal equilibrium between vapor diffusion and active photothermal surface area, resulting in a peak mass loss of approximately 1.75 kg/m² under 1 sun illumination. This layout markedly surpassed 2 mm, 10 mm, and non-channeled designs in both photothermal and convection-driven circumstances. This study presents a scalable and efficient approach to improving solar desalination by structural micro-environment alteration.